Barbastella barbastellus ... - Honacki, James H.; Kinman, Kenneth E.; Koeppl, James W. (Zenodo, 1982)
Barbastella barbastellus (Schreber, 1774). Saugethiere, 1:168. TYPE LOCALITY: France, Burgundy. DISTRIBUTION: England and W. Europe to Caucasus; Turkey; Crimea; Morocco; larger Mediterranean islands; perhaps Senegal. ISIS NUMBER: 5301405014002001001. ... : Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Chiroptera, pp. 111-215 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 170, DOI: 10.5281/zenodo.7352990 ...